Necessity of the Social Moral Education - Kalenda, Česlovas (Problemos, 1971)
In the paper historical prerequisites of the emergence of social moral education as the social phenomenon are analysed. When the individual had come to satisfy his requirements on the basis of private property the immediate relation between the individual and the collective body disappeared. Under the conditions of complicated social structure and estrangement of human relations, behaviour regulation of the individual, the combination of his private interests with social ones formed a special social problem. As a result of this morals was singled out of the totality of customs and the necessity of social moral education arose. Partly, due to the necessity factor morals extended its significance beyond the definite realm of customs to the totality of the desired behaviour standards. The specific character of moral imperatives under the conditions of estrangement, the role of religion and ethical theory in the process of moral education are underlined in the paper.